2021
DOI: 10.12927/hcpol.2021.26655
|View full text |Cite
|
Sign up to set email alerts
|

The Induced Productivity Decline Hypothesis: More Physicians, Higher Compensation and Fewer Services

Abstract: The Induced Productivity Decline Hypothesis: More Physicians, Higher Compensation and Fewer Services has increased but compensation has not kept pace), physicians are experiencing a "reverse wage-productivity gap" whereby compensation is increasing but productivity is decreasing, resulting in more physicians, higher compensation and fewer services. We conclude by discussing potential policy options to address how best to provide timely access to medical care for Canadians while keeping physician healthcare exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…The overall trend of declining primary care services over time is a somewhat unexpected observation, particularly given an aging population and greater complexity in community-based service delivery. This is, however, consistent with persistent reports of primary care access challenges [ 63 ] and declining family physician visit volume described elsewhere [ 64 ]. Taken together, findings point to a need for substantial policy changes in primary care to address both declining access overall, and increasing inequity in access.…”
Section: Discussionsupporting
confidence: 91%
“…The overall trend of declining primary care services over time is a somewhat unexpected observation, particularly given an aging population and greater complexity in community-based service delivery. This is, however, consistent with persistent reports of primary care access challenges [ 63 ] and declining family physician visit volume described elsewhere [ 64 ]. Taken together, findings point to a need for substantial policy changes in primary care to address both declining access overall, and increasing inequity in access.…”
Section: Discussionsupporting
confidence: 91%
“… 26 Another possible explanation is that the proposal that compensation increases exceeding target incomes have caused a cut-back in service provision. 27 , 28 …”
Section: What Does This Analysis Mean For Physician Workforce Plannin...mentioning
confidence: 99%
“…26 Another possible explanation is that the proposal that compensation increases exceeding target incomes have caused a cutback in service provision. 27,28 Although our analysis is informative, it and the 2 simple adjustments we employed have limitations. For example, we held service provision per age-sex group constant at its 1996 level.…”
Section: What Does This Analysis Mean For Physician Workforce Plannin...mentioning
confidence: 99%
“…The research paper by Lee et al (2021) provides an analysis of the conundrum facing provinces' governments: an increasing number of physicians and continuing struggles for residents to access primary and specialty care. Based on analyses of retrospective administrative datasets, the study found that the number of physicians has been increasing over the past five years even though the volume of services physicians has been providing to their patients has been declining.…”
Section: In This Issuementioning
confidence: 99%
“…L' article de Lee et al (2021) fournit une analyse de l'énigme à laquelle sont confrontés les gouvernements provinciaux : un nombre croissant de médecins, certes, mais pourtant les efforts continuent sans cesse pour que les résidents aient accès aux soins primaires et spécialisés. Sur la base d' analyses d' ensembles de données administratives rétrospectives, l'étude révèle que le nombre de médecins a augmenté au cours des cinq dernières années, même si le volume de services fournis par les médecins à leurs patients a diminué.…”
Section: Dans Ce Numérounclassified